Age and growth of Aphia minuta (Pisces, Gobiidae) from the central Adriatic Sea - M. La Mesa (Scientia Marina, 1999)
Aphia minuta (Risso, 1810) is by far the most common pelagic gobiid of the Adriatic Sea and it is seasonally exploited by some local small-scale fishing fleets. Despite this, very few data on its biology in this area have been reported to date. Accordingly, age and growth of A. minuta were investigated by counting microincrements (daily rings) in the sagittal otoliths of 262 specimens caught in the central Adriatic between May 1996 and March 1997. Age of fish from 14 to 55 mm total length ranged between 42 and 275 days, confirming the short life span of this species. The von Bertalanffy growth parameters estimated by the age-length data pairs for the whole population were: L = 68.7 mm; K = 1.55 year-1; t0 = 0.077 year. The analysis of the monthly length-frequency distributions showed the simultaneous presence in late spring-early summer of two main cohorts which, together with the back-calculated hatch date distribution, indicated a more extended spawning period than previously reported in the literature. Because the fishery for A. minuta in the central Adriatic exploits the spawning stock it should be monitored and, if necessary, regulated.